Spektroscopi FTIR dan sifat mekanik nanokomposit grafting HDPE dan nanoprecipitated calcium carbonate (NPCC) - Yuniari, Arum; Kasmudjiastuti, Emiliana (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2012)
ABSTRACTThe purpose of this research based on high density polyethylene (HDPE) and nanoprecipitated calciumcarbonate (NPCC) was to evaluate the effect of nanoprecipitated calcium carbonate (NPCC) on FTIR spectroscopy and mechanical properties. The nanocomposites was prepared with a rheomix 3000 Haake at 180 º C and 50 rpm of rotor speed for 10 minutes. The composition of HDPE and additives were permanently, and NPCC content varied 10, 15, 20, 30, 40 and 50 phr (per hundred resin) respectively and control was made inherent NPCC. The nanocomposites were characterized using tensile strength, hardness tester, electro densimeter and Fourier Transform Infra Red (FTIR) spectroscopy techniques. The results of mechanical properties showed that the increasing the amount of NPCC was able increase hardness and density while elongation at break more stable and tensile strength decreased. Analysis functional group on nanocomposites with Fourier Transform Infra Red (FTIR) indicated a new peak on wave band 3472,49 cm-1 (OH stretching).ABSTRAKPenelitian tentang pembuatan nanokomposit dari bahan high density polyethylene(HDPE) dan nanoprecipitated calciumcarbonate (NPCC) bertujuan untuk mengetahui pengaruh penambahan filler NPCC terhadap sifat mekanik dan spektroscopi. Nanokomposit dibuat dengan Rheomix 3000 Haake pada suhu 180oC dan kecepatan 50 rpm selama 10 menit. Komposisi HDPE dan bahan aditif dibuat tetap, dan kandungan NPCC divariasi berturut-turut 10 ; 20 ; 30; 40 dan 50 phr (per hundred resin) dan dibuat kontrol tanpa ditambah NPCC. Sifat mekanik diuji dengan alat ujitensile strength, hardness, densimeter dan karakterisasi gugus fungsi ditentukan menggunakan Fourier Transform Infra Red (FTIR). Hasil uji sifat mekanik menunjukkan semakin tinggi jumlah NPCC kekerasan dan densitas naik, kemuluran tetap sedangkan kuat tarik cenderung turun. Spektrum nanokomposit HDPE/NPCC menunjukkan terjadinya puncak baru pada bilangan gelombang 3472,49 cm-1 (OH stretching).